Az információs müveltség változó szempontjai a 2.0-ás kutatási kornyezetben - Špiranec, Sonja (2013)
New research environments, which are a result of technological innovations initiated by the Web 2.0, have the potential to change the very principles of science and research. These principles are characterized by new patterns of generating, managing and using scholarly information, necessitating complementary changes in Information literacy as well. In the paper the author analyzes shifting aspects of IL training for researchers who operate in research environments pervaded by Web 2.0 tools and social media. Although the use of new tools and media generate a range of issues in all areas of human endeavour, domains like research and scholarship encounter specific challenges resulting from the use of Web 2.0 tools and services. Based on literature review and analysis of issues caused by “Research 2.0 trends”, the paper highlights main features of shifts in conceptualizing IL training for researchers.
Projekt MZOS
ENG